2020
DOI: 10.1534/genetics.120.303776
|View full text |Cite
|
Sign up to set email alerts
|

Survival Following Traumatic Brain Injury in Drosophila Is Increased by Heterozygosity for a Mutation of the NF-κB Innate Immune Response Transcription Factor Relish

Abstract: Traumatic brain injury (TBI) pathologies are caused by primary and secondary injuries. Primary injuries result from physical damage to the brain, and secondary injuries arise from cellular responses to primary injuries. A characteristic cellular response is sustained activation of inflammatory pathways commonly mediated by NF-κB transcription factors. Using a Drosophila melanogaster TBI model, we previously found that the main proximal transcriptional response to primary injuries is triggered by activation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 121 publications
(157 reference statements)
3
10
0
Order By: Relevance
“…Our data shows that mild TBI causes synergistic effects on mortality after a requisite number of injuries, possibly because cumulative cellular stress surpasses a critical threshold. We expect that many of the secondary injury pathways active in animals following our mild TBI (60°) methodology overlap with pathways previously reported (Katzenberger et al 2015; Katzenberger et al 2016; Anderson et al 2018; Saikumar et al 2020; Swanson, Rimkus, et al 2020; Swanson, Trujillo, et al 2020). However, the identity of any specific factor(s) which set or scale the sensitivity to rmTBI remain unknown.…”
Section: Descriptionsupporting
confidence: 62%
“…Our data shows that mild TBI causes synergistic effects on mortality after a requisite number of injuries, possibly because cumulative cellular stress surpasses a critical threshold. We expect that many of the secondary injury pathways active in animals following our mild TBI (60°) methodology overlap with pathways previously reported (Katzenberger et al 2015; Katzenberger et al 2016; Anderson et al 2018; Saikumar et al 2020; Swanson, Rimkus, et al 2020; Swanson, Trujillo, et al 2020). However, the identity of any specific factor(s) which set or scale the sensitivity to rmTBI remain unknown.…”
Section: Descriptionsupporting
confidence: 62%
“…In mammalian TBI models, reduced NF-κB activity resulting from treatment with the PPARγ agonist pioglitazone or other pharmacological agents improves outcomes [ 22 25 , 41 46 ]. Reducing NF-κB activity also improves TBI outcomes in flies [ 33 ]. Heterozygosity for a null mutation of Relish , one of three NF-κB genes in Drosophila , reduces early mortality and increases lifespan following TBI.…”
Section: Discussionmentioning
confidence: 99%
“…Second, we previously found that flies fed water versus CMYD exhibited increased expression of AMP genes following TBI, suggesting that the beneficial effects of water are not mediated by inhibition of Relish, which activates the transcription of AMP genes [ 29 ]. Third, while heterozygosity for a mutation of Relish reduced the incidence of early mortality for flies fed CMYD following TBI, it did not affect the incidence of early mortality for flies fed water following TBI, suggesting that water functions either downstream or independently of Relish [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations